2015
DOI: 10.1038/onc.2015.325
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA-binding protein HuR promotes hypoxia-induced chemoresistance through posttranscriptional regulation of the proto-oncogene PIM1 in pancreatic cancer cells

Abstract: Previously, it has been shown that pancreatic ductal adenocarcinoma (PDA) tumors exhibit high levels of hypoxia, characterized by low oxygen pressure (pO2) and decreased O2 intracellular perfusion. Chronic hypoxia is strongly associated with resistance to cytotoxic chemotherapy and chemoradiation in an understudied phenomenon known as hypoxia-induced chemoresistance. The hypoxia-inducible, pro-oncogenic, serine-threonine kinase PIM1 (Proviral Integration site for Moloney murine leukemia virus 1) has emerged as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(146 citation statements)
references
References 70 publications
(129 reference statements)
2
144
0
Order By: Relevance
“…Various cancer-associated stressors can induce this HuR cytoplasmic translocation including hypoxia (29), glucose deprivation (18), DNA damaging agents (33), anti-DR5 mAb (6) and gemcitabine (34). To determine whether TRAIL treatment of PDA cells can induce HuR translocation from the nucleus to the cytoplasm, we performed immunoblot analysis of cytoplasmic extracts from PDA cells treated with increasing doses of sTRAIL and discovered a more than 2-fold increase in cytoplasmic HuR levels in BxPc-3 cells treated for 3 h at 40 ng/ml of sTRAIL, compared to untreated samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various cancer-associated stressors can induce this HuR cytoplasmic translocation including hypoxia (29), glucose deprivation (18), DNA damaging agents (33), anti-DR5 mAb (6) and gemcitabine (34). To determine whether TRAIL treatment of PDA cells can induce HuR translocation from the nucleus to the cytoplasm, we performed immunoblot analysis of cytoplasmic extracts from PDA cells treated with increasing doses of sTRAIL and discovered a more than 2-fold increase in cytoplasmic HuR levels in BxPc-3 cells treated for 3 h at 40 ng/ml of sTRAIL, compared to untreated samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To authenticate a direct association between DR4 mRNA and HuR, and to localize the site of interaction, constructs containing the 5′- or 3′-UTR of DR4 subcloned immediately upstream or downstream, respectively, of the Renilla reporter gene of psiCHECK2 vector. These reporter constructs were then transfected into Panc-1 cells, as previously described (6, 29, 33). We determined by RT-qPCR that the total input RNA for the RNP-IP contained equivalent DR4 and PIM1 sequences (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed an increase in p21 expression in hypoxia-treated T3M4 and CD18/HPAF cells, suggestive of growth arrest of PC cells (Supplementary Figure 3A), which was corroborated by our growth kinetics analysis in hypoxia-treated and untreated CD18/HPAF cells (Figure 5b) and by a recent study where hypoxia has shown to cause growth inhibition in PC cell lines. 30 To assess the role of ROS on pAkt reduction, we analyzed its expression in the presence and absence of NAC. Interestingly, hypoxia-mediated downregulation of pAkt in CD18/HPAF cells was abolished upon NAC administration, further emphasizing that the reduction in pAkt levels under hypoxia is ROS dependent (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
“…HuR, an RBP, has already been shown to mediate post-transcriptional regulation in various cancers [13,14] and is known to interact with a substantial body of RNA transcripts [15,16]. Subsequent studies reported the collaborative [17] or suppressive [18] interplay between HuR and miRNA in many cancers.…”
Section: Introductionmentioning
confidence: 99%